2017
DOI: 10.1111/jpc.13678
|View full text |Cite
|
Sign up to set email alerts
|

Survival and neurodevelopmental outcomes in extremely preterm infants 22–24 weeks of gestation born in Western Australia

Abstract: At these gestations, survival figures varied markedly with the chosen population denominator. Regional data are essential for valid population comparison. While many developmental difficulties occurred in these children, 78% were free from moderate or severe impairment at ages 3-5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…8 In the WA study, 152 of 159 (96%) survivors were seen in follow-up at a median age of 59 months. 9 Rates of severe physical disability were relatively low, with only three (2%) children experiencing moderate to severe cerebral palsy (GMFCS 111-V) and two (1.3%) children with blindness. In contrast, 27 (18%) children were identified with moderate or severe cognitive disability (IQ more than 2SD below the mean), and 9 (5.9%) children were diagnosed with autism.…”
Section: Survival But At What Cost?mentioning
confidence: 96%
See 3 more Smart Citations
“…8 In the WA study, 152 of 159 (96%) survivors were seen in follow-up at a median age of 59 months. 9 Rates of severe physical disability were relatively low, with only three (2%) children experiencing moderate to severe cerebral palsy (GMFCS 111-V) and two (1.3%) children with blindness. In contrast, 27 (18%) children were identified with moderate or severe cognitive disability (IQ more than 2SD below the mean), and 9 (5.9%) children were diagnosed with autism.…”
Section: Survival But At What Cost?mentioning
confidence: 96%
“…Sharp and colleagues provide important outcome data for infants born alive at 22–24 weeks’ gestation in Western Australia (WA) . A major strength of this study is the provision of denominators for survival for all live births and not just those who received neonatal intensive care.…”
Section: Neonatal Intensive Care Unit Admission Rates Following Live mentioning
confidence: 99%
See 2 more Smart Citations
“…Sharp et al reported that >50% of preterm infants born at <24 weeks of gestation in Western Australia showed no major disability, including cerebral palsy and ASD. 33 The median age at diagnosis was 59 months. 33 The study did not examine the risk of mild disability and school problems.…”
Section: Disability-free Survival In Very Preterm Infantsmentioning
confidence: 99%